STUDI FENOMENOLOGI FILM ANIMASI UPIN DAN IPIN DI MNC TV DALAM MEMBENTUK PERILAKU IMITASI PADA ANAK DI TK AL-MUHIBBIN KECAMATAN SUMBER KABUPATEN CIREBON - Ana Lufita Sari; Hery Nariyah; Welly Wihayati (JURNAL SIGNAL, 2019)
ABSTRACT           Upin and Upin animation is an animation aired by MNC TV station and produced by Les't Copaque and began airing in 2007 aimed at welcoming the holy month of Ramadan, which airs at 5.00 pm. This animation carries a story to educate children about the meaning and importance of the holy month of Ramadan. Animation Upin and Ipin tell about the world of children full of fun and diversity, all the stories told in animation Upin and Ipin provide education to children about the life of society, togetherness and mutual respect between each other and against the elderly. This animation teaches children to be a better person and always thinking optimistic for the future. Animation Upin and Ipin have many educational aspects for children. The style of the language and the motivation to learn to achieve these goals are potentially imitated or can shape imitation behavior for the child. The purpose of this study are: (1) To find out how the animated film Upin and Ipin that aired on MNC TV; (2) To know the child's behavior in watching Upin and Ipin Animation Movies on MNC TV; (3) And to know what efforts made by parents to accompany their children in watching Upin and Ipin Animated Movies on MNC TV. The research method used is phenomenology study method. The research concept identifies Upin and Ipin animated films aired on MNC TV, to know the behavior of the kindergarten children of AL-Muhibbin Sources when watching the Animation Upin and Ipin films on MNC TV, and to find out what efforts are made by parents to assist his son in watching Animation Upin and Ipin for child's imitation behavior can be controlled with the guidance and assistance of parents. The conclusion of the research on the Phenomenology of Upin and Ipin Animation films in shaping imitation behavior in children is Upin and Ipin Animation has an interesting storyline, tells about the good life of society and tells about the playground of children full of fun. Involvement on Upin and Ipin animation shows among the Kindergarten children AL-Muhibbin Sumber Cirebon relates to time, duration and presentation. Imitation behavior performed by the child including into positive and negative imitation behavior in children, is said to be negative because of the fear of local language refraction (original) which is replaced with the language used in animation Upin and Ipin (Malay) imitation in terms of language style and said positive because animation Upin and Ipin can motivate children in learning and ideas. Parents' efforts to ensure the child's imitation behavior can be controlled by accompanying and guiding the child while watching the Upin and Ipin Animation films. Keywords: Upin and Ipin Animation Movies, Imitation Behavior Formation.